Clinical efficacy and safety of Chinese herbal injections in combination with platinum-based chemotherapy for advanced non-small cell lung cancer: a systematic review and meta-analysis of 140 randomized controlled trials - Cao, Kangdi; Hu, Shuaihang; Wang, Dandan; Qiao, Chenxi; Wang, Zhuo; Wang, Jinkun; Hou, Wei (Frontiers in Oncology, 2024)
Background and Aim: Chinese herbal injection (CHI) is a widely used preparation for advanced non-small cell lung cancer (NSCLC) treatment to alleviate the adverse drug reactions and enhance the clinical efficacy of chemotherapy. However, its efficacy and safety in combination with platinum-based chemotherapy (PBC) remain poorly understood owing to the lack of high-level evidence in the face of a wide variety of CHIs. Therefore, in this study, we aimed to explore the efficacy and safety of CHIs in combination with PBC regimens in the treatment of mid- and advanced NSCLC. Methods: Systematic evaluation and meta-analysis were conducted as per the Preferred Reporting Project for Systematic Evaluation and Meta-Analysis Protocols (PRISMA-P). Seven databases were comprehensively searched for relevant randomized controlled trials (RCTs) through August 1, 2022. The quality of each study was evaluated based on the Cochrane Handbook for Systematic Reviews of Interventions. Statistical analysis was performed using Revman 5.3, with dichotomies expressed as risk ratio (RR) and 95% confidence interval (CI). Objective response rate (ORR) and disease control rate (DCR) were selected as the primary outcomes, with quality of life (QoL) and toxic side effects as secondary outcomes. Results: A total of 140 RCTs were included in this study. The results of the meta-analysis suggested that, compared with PBC alone, PBC combined with CHIs significantly improved the ORR (RR=1.35, 95% CI: 1.30–1.41, P<0.001), DCR (RR=1.15, 95% CI: 1.13–1.18, P<0.001) and QoL (RR=1.29, 95% CI: 1.24–1.33, P<0.001). Moreover, the combination treatment reduced chemotherapy-induced leukopenia (RR=0.69, 95% CI: 0.64–0.75, P<0.001), anemia (RR=0.70, 95% CI: 0.62–0.79, P<0.001), thrombocytopenia (RR=0.68, 95% CI: 0.62–0.75, P<0.001), nausea and vomiting (RR=0.69, 95% CI: 0.63–0.76, P<0.001), diarrhea (RR=0.59, 95% CI: 0.48–0.73, P<0.001), and constipation (RR=0.68, 95% CI: 0.54–0.86, P=0.001). Conclusions: According to the available evidence, CHIs in combination with PBC can improve clinical efficacy and reduce the toxic side effects in the treatment of advanced NSCLC. However, considering the study's limitations, more rigorous and high-quality studies are needed to further confirm the results.